Epidemiological profile of breast cancer mortality in the state of Mato de Grosso, Brazil, from 2011 to 2021 (Research, Society and Development, 2023)
Objective: To analyze and describe the epidemiological profile of breast cancer mortality in the State of Mato Grosso (MT), Brazil, from 2011 to 2021. Methodology: The data were collected from the Mato Grosso State Health Secretariat Portal and analyzed using Microsoft Excel 2016 and SPSS software. Result: A significant increase of 60% in the number of deaths from breast cancer in MT over the study period. In 2021, there was the highest absolute frequency (11.2%), with females being the most affected (98.3%). The age groups of 50 to 59 years, 60 to 69 years, and 40 to 49 years together accounted for 66.6% of deaths. The brown race represented 49.8% of the deaths, and individuals with 8 to 11 years of education had the highest mortality rate (25.9%). The underlying cause of unspecified breast cancer classification represented 85% of the deaths, and 75% of the victims received medical assistance. Notably, 96.1% of the deaths due to breast cancer did not have an outpatient investigation. The Central-North macro-region, including the city of Cuiabá, accounted for 51.8% of the deaths. Occupations in Group 4 and 5 accounted for 72.9% of breast cancer deaths. Conclusion: Breast cancer mortality in MT exhibits peculiarities compared to the national reality, particularly in terms of race/color and years of education, due to socioeconomic factors and the natural history of the disease. However, most of the analyzed variables showed a similar mortality trend to breast cancer epidemiology in Brazil.